The IX Iberian Congress of Ichthyology 2022
DOI: 10.3390/blsf2022013107
|View full text |Cite
|
Sign up to set email alerts
|

Living on the Edge: Management and Conservation of Atlantic Salmon at the Southern Limit of the Species Distribution

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An examination of the key informants' perceptions of landscape justice provided insights into land and water management issues and revealed the need for participatory management approaches in the case of Atlantic salmon, which should be further developed. This is because participatory management approaches have shown potential across Europe and beyond to foster mutual understanding and increase local knowledge to inform decision making on the sustainable management of river catchments, including Atlantic salmon fishing activities [54,55]. We found that state governance affects the formation of, but is, therefore, also responsible for managing, the social, cultural, and economic risks.…”
Section: Discussionmentioning
confidence: 90%
“…An examination of the key informants' perceptions of landscape justice provided insights into land and water management issues and revealed the need for participatory management approaches in the case of Atlantic salmon, which should be further developed. This is because participatory management approaches have shown potential across Europe and beyond to foster mutual understanding and increase local knowledge to inform decision making on the sustainable management of river catchments, including Atlantic salmon fishing activities [54,55]. We found that state governance affects the formation of, but is, therefore, also responsible for managing, the social, cultural, and economic risks.…”
Section: Discussionmentioning
confidence: 90%